MEDIATION OF WORK DISCIPLINE ON INFLUENCE TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION FOR THE PERFORMANCE OF STATE ELEMENTARY SCHOOL TEACHERS IN GAPURA DISTRICT, SUMENEP REGENCY - Faishal Habsyi; Syunu Trihantoyo; Ainur Rifqi; Amrozi Khamidi (LP2M IAI Al-Khairat Pamekasan, 2026)
Teacher performance is a critical element in improving the quality of education. This study analyzes the direct and indirect effects of transformational leadership and work motivation on teacher performance, with work discipline as a mediating variable. The research employs a quantitative approach with an explanatory survey design. The population consisted of all teachers in State Elementary Schools of Gapura District, Sumenep Regency, with a sample of 114 teachers selected through proportionate random sampling. Data were collected using closed questionnaires and analyzed using variance-based Structural Equation Modeling (SEM) with SmartPLS 4. The results show that transformational leadership has a positive and significant effect on teacher performance (β=0.424), work motivation has a positive and significant effect on teacher performance (β=0.271), and work discipline significantly mediates the relationship between transformational leadership and teacher performance (β=0.211). However, work discipline does not mediate the relationship between work motivation and teacher performance. The study concludes by emphasizing the importance of transformational leadership in improving teacher discipline and performance. Recommendations include the need for transformational leadership development programs for school principals and the strengthening of motivation systems based on recognition and teacher career development.